2020
DOI: 10.1186/s40359-020-00445-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Needs Assessment of Family Caregivers-Cancer scale in an Asian population

Abstract: Background: The Needs Assessment of Family Caregivers-Cancer (NAFC-C) scale is shown to have adequate psychometric properties in assessing family caregiver needs during the cancer journey and its psychometric properties have been studied only in Western populations. This study sought to validate the NAFC-C in an Asian population for wider applicability. Methods: Participants (n = 363) completed questions on sociodemographics, the Depression Anxiety Stress Scale, the Zarit Burden Interview, the Caregiver Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(90 reference statements)
1
5
0
Order By: Relevance
“…The NAFC-C was originally developed with the United States population, which has very different population characteristics than the Singapore population ( 3 ). This was also shown in our previous validation study as FCCs may interpret items differently from their United States counterpart ( 21 ). Hence, other than differences in characteristics of needs, there may be other unexplored needs specific to the Asian population.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The NAFC-C was originally developed with the United States population, which has very different population characteristics than the Singapore population ( 3 ). This was also shown in our previous validation study as FCCs may interpret items differently from their United States counterpart ( 21 ). Hence, other than differences in characteristics of needs, there may be other unexplored needs specific to the Asian population.…”
Section: Discussionsupporting
confidence: 81%
“…The scale consists of four factors (1) psychosocial unmet needs, (2) unmet medical needs, (3) unmet financial needs, and (4) daily activity unmet needs. Our previous study found acceptable validity of the NAFC-C to be used in an Asian population like Singapore ( 21 ). In this sample, Cronbach's alpha was strong (α = 0.90).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…These four factors are further divided into eight subscales. The NAFC-C has been previously validated and shown good reliability in an Asian population [25]. Of interest in this study are the subscales of the daily activity unmet needs, which examined caregiver personal care ('getting help from others in order to take time for yourself'), and role management for survivor care ('balancing work/school with caring for him/her').…”
Section: Methodsmentioning
confidence: 99%